Survey on Prevalence of Gastrointestinal Parasites in Fighting Cock in the Northeast of Thailand - Vaisusuk, Kotchaphon; Chatan, Wasupon (Journal of Mahanakorn Veterinary Medicine, 2022)
The present study was carried out on fighting cock to determine the prevalence and species diversity of gastrointestinal parasites in Northeast of Thailand. Of the total 390 fighting cock collected from different villages of Northeast. Feces samples were processed and examined using formalin – ethyl acetate concentration technique (FECT). The results showed the prevalence of gastrointestinal parasites infection in fighting cock was 52% (203/390). The results showed that chickens were infected with nine kinds of gastrointestinal parasites which comprised of A. Golli (48.3%) H. Gallinarum (36.5%) A. Duodenale (28.1%) S. Stercoralis (20.7%) R. Tetragona (18.2%) T. Trichiura (16.7%) Eimeria spp. (14.8%) Capillaria spp. (7.4%) and E. Revolutum (4.4%) However, educating and advising servicesfarmers on production system and management will be way to reduce the incidence of disease in fighting cock in the future.